Application of Corporate Crime Sanctions in Pornography Crimes (Study of the Porn Film Industry and Trade) (International Journal of Scientific Research and Management (IJSRM), 2024)
The development of information and communication technology has contributed to the increase in the creation and dissemination of pornography which has had a negative influence on the morals and noble personality of the Indonesian people. In relation to the era of globalization, the existence of a corporation has a big contribution to the interests of the country and its citizens. The existence of corporations is often accompanied by violations, including violations of criminal law, one of which is the case of the pornographic film industry and trade. The authors examine the criteria for criminal acts of pornography which are classified as corporate crimes and how sanctions are applied for criminal acts of pornography as a corporate crime. This research uses normative-empirical juridical methods and analytical descriptive research specifications. Based on the research results, it can be concluded that the criteria for criminal acts of pornography which are classified as corporate crimes are non-violent, corrosive effect, and have a very detrimental impact on society at large. The industry and trade in pornographic films is a form of criminal corporation/organization, and there has never been a court decision regarding sanctions for corporate criminal acts applied to cases of criminal acts of pornography. Efforts that can be made to overcome this problem are to harmonize the definition of a corporation, create clear criteria for corporations as subjects of criminal law, need to hold Focus Group Discussions (FGD) among academics and law enforcement officials, and apply sanctions against perpetrators of criminal acts of pornography which are classified as corporate crimes.